Protein-mediated bioadhesion in marine organisms: A review. (August 2021) - Li, Xi; Li, Shiguo; Huang, Xuena; Chen, Yiyong; Cheng, Jiawei; Zhan, Aibin
Abstract: Protein-mediated bioadhesion is one of the crucial physiological processes in marine organisms, by which they can firmly adhere to underwater substrates. Most marine adhesive organisms are biofoulers, causing negative effects on marine ecosystems and huge economic losses to aquaculture and maritime industries. Furthermore, adhesive proteins in these organisms are promising bionic candidates for high-performance artificial materials with great application value. In-depth understanding of the bioadhesion in marine ecosystems is of dual significance for resolving biofouling issue and developing marine bionic products. Here, we review the research progress of protein-mediated bioadhesion in marine organisms. The adhesion processes such as protein biosynthesis and secretion are similar among organisms, but the detailed features such as compositions, structures, and molecular functions of adhesive proteins are distinct. Hydroxylation, glycosylation, and phosphorylation are important post-translational modifications during the processes of adhesion. The contents of some amino acids such as glycine, tyrosine and cysteine involved in underwater adhesion are significantly higher, which is a sequence feature of barnacle cement and mussel foot proteins. The amyloid structures and conserved domains/motifs such as EGF and vWFA distributed in adhesive proteins are involved in the underwater adhesion. In addition, the oxidative cross-linking also plays an important role in marine bioadhesion. Overall, the unique and common features identified for the protein-mediated bioadhesion in diverse marine organisms here provide background information and essential reference for characterizing marine adhesive proteins and associated functional domains, formulating antifouling strategies, and developing novel biomimetic adhesives. Graphical abstract: Image 1 Highlights: Most marine organisms adhere to substrates by protein-mediated mechanisms. Diverse adhesive proteins have common characteristics. Common adhesive protein features include domains, modifications and amino acids. Processes for adhesive proteins include complex biosynthesis and secretion. Protein-mediated bioadhesion is of great significance for antifouling and bionics.